Legal dilemmas about mandatory childhood vaccination in Europe - Czechowicz, Sebastian (Medicine, law & society, 2023)
Compulsory childhood and adolescent vaccination are a controversial issue in the public arena. They also pose a challenge on the ground of legal sciences. This article is devoted to a dogmatic-legal analysis of the type of legally protected goods that are restricted in connection with mandatory vaccination (among others: the right to respect for private and family life, personal freedom, the right to self- determination) and those values that vaccination is in principle supposed to protect (public health, life, and health of children). The article analyses in detail the ruling of the European Court of Human Rights, which seems to be a breakthrough. On the one hand, it ends the dispute pending before the Court and, on the other, it opens the field for further discussion on the essence of mandatory vaccinations. The research has been carried out by using the dogmatic-legal method, the method of analysis and criticism of literature, the method of analysis of case law and the statistical method. In the presented research results, reports and statistical data of international bodies concerning the level of vaccination among children and adolescents in Europe were used.
Keywords: child; countering the spread of communicable diseases; človekove pravice; European Court of Human Rights; Evropsko sodišče za človekove pravice; fundamental rights; javno zdravje; otroci; otroške bolezni; public health; vakcinacija